An Algorithm for Concurrent Use of Quantum Simulators and Computers in the Context of Subgraph Isomorphism - Gheorghica, Radu-Iulian (SACI (International Symposium on Applied Computational Intelligence and Informatics. Online), 2023)
Quantum computers represent the new generation of computing. But despite this, they have a limit which consists of the number of qubits, or quantum bits, that each computer has at its disposal. The purpose of this research is the ability to use multiple quantum simulators and computers in order to achieve calculations made by a unified number of qubits. The design for this algorithm makes use of parallel and distributed programming. The key results are amplified amplitudes obtained for large quantum circuits that would otherwise be impossible to execute on a single quantum computer whose available number of qubits is exceeded by the one of such circuits. Thus the algorithm presented in the current paper has been designed and tested, showing favorable results. A 25 qubit circuit was used for the test cases. It was partitioned in multiple smaller circuits that were sent for execution from a laptop, directly to the quantum devices. The circuit number of qubits can be increased as considered necessary by the user.